2018
DOI: 10.1242/dev.163394
|View full text |Cite
|
Sign up to set email alerts
|

Lmx1a is required for the development of the ovarian stem cell niche in Drosophila

Abstract: The ovary serves as a model for pioneering studies of stem cell niches, with defined cell types and signaling pathways supporting both germline and somatic stem cells. The establishment of the niche units begins during larval stages with the formation of terminal filament-cap structures; however, the genetics underlying their development remains largely unknown. Here, we show that the transcription factor Lmx1a is required for ovary morphogenesis. We found that Lmx1a is expressed in early ovarian somatic linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Indeed, we found that when En/Inv were depleted in developing niches by RNAi, the same number of correctly formed TFs, TF cells and CCs were found as in controls. This is consistent with the observation of normal larval ovaries upon En/Inv depletion in Allbee et al (Allbee et al, 2018), using a different niche cell Gal4 driver and the same en/inv RNAi transgenes as used in our study. In contrast, another study, based on induction of clones of ovarian somatic cells homozygous for a null allele for both en/inv, concluded that these genes are involved specifically for proper TF cell alignment within individual stacks in larval ovaries (Bolívar et al, 2006).…”
Section: En/inv Are Not Essential For Tf Formation Nor Gsc Establishmsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, we found that when En/Inv were depleted in developing niches by RNAi, the same number of correctly formed TFs, TF cells and CCs were found as in controls. This is consistent with the observation of normal larval ovaries upon En/Inv depletion in Allbee et al (Allbee et al, 2018), using a different niche cell Gal4 driver and the same en/inv RNAi transgenes as used in our study. In contrast, another study, based on induction of clones of ovarian somatic cells homozygous for a null allele for both en/inv, concluded that these genes are involved specifically for proper TF cell alignment within individual stacks in larval ovaries (Bolívar et al, 2006).…”
Section: En/inv Are Not Essential For Tf Formation Nor Gsc Establishmsupporting
confidence: 92%
“…In order to explore possible functional interactions between Bab and En/Inv proteins, we tested whether en/inv expression in niche cells of prepupal ovaries depends on Bab proteins. It has been reported that en/inv are specifically expressed in GSC niche cells as of the beginning of TF formation in the larval ovary (Allbee et al, 2018;Forbes et al, 1996;Green and Extavour, 2012;Mendes and Mirth, 2016). In addition, we found here a significant difference in En/Inv levels between TF cells and CCs in control prepupal niches (hs-FLP; FRT-bab AR07 /FRT-GFP and hhG>GFP, Fig 7A and 7A' and Fig 7B and 7B', green and yellow brackets, respectively), with a three-fold higher level in control TF cells than CCs (hs-FLP; GFP, Fig 7D).…”
Section: The Functions Of Bab1 and Bab2 Are Not Required In Niche Celmentioning
confidence: 99%
See 1 more Smart Citation
“…TF specification requires the expression of engrailed (En) ( Bolívar et al, 2006 ) and the transcription factors Bab1 and Bab2, encoded by the bric-à-brac locus ( Couderc et al, 2002 ; Godt et al, 1993 ). A third transcription factor, Lmx1a, was recently found to be necessary for the specification of the TFCs ( Allbee et al, 2018 ). Our hpo[RNAi] Ovariole Number sub-network identifies numerous additional novel transcription factors including bunched ( bun ) and retinoblastoma-family protein ( rbf ), which we hypothesise could also be involved in the specification of ovariole number.…”
Section: Discussionmentioning
confidence: 99%
“…Induced expression of LXM1B could rescue the signature of LMX1A loss-of-function. Thus both these genes could play a role in the development of ovary [ 70 ]. The role of LMX1B has not been thoroughly evaluated in any tumor type.…”
Section: Introductionmentioning
confidence: 99%